1970
DOI: 10.3329/jafmc.v5i2.4580
|View full text |Cite
|
Sign up to set email alerts
|

Visual Outcome after Nd:YAG Laser Capsulotomy

Abstract: A longitudinal study was carried out in the laser unit of the Combined Military Hospital (CMH), Dhaka on 500 eyes of 500 patients who were treated with Neodymium-yttrium-aluminium-garnet (Nd:YAG) laser capsulotomy over a period of two and a half years. The aim of this study was to evaluate the visual acuity following Nd:YAG laser capsulotomy. The main entry criteria for this study were posterior capsular opacification (PCO) following Extracapsular Cataract Extraction (ECCE). The patients with corneal opacity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
2
2
0
Order By: Relevance
“…Likewise, Terry et al 21 and Aron-Rosa et al 22 reported visual improvement in 92%, and 94% of their cohorts, respectively. Regarding the changes in the spherical refractive error, several studies had reported that the change in the spherical error after YAG-PC was statistically insignificant, 20,[23][24][25] in agreement with our results in the non-FECD group. In the FECD eyes, there was a significant hyperopic shift compared to the controls in the 1st month and 3rd months after laser.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Likewise, Terry et al 21 and Aron-Rosa et al 22 reported visual improvement in 92%, and 94% of their cohorts, respectively. Regarding the changes in the spherical refractive error, several studies had reported that the change in the spherical error after YAG-PC was statistically insignificant, 20,[23][24][25] in agreement with our results in the non-FECD group. In the FECD eyes, there was a significant hyperopic shift compared to the controls in the 1st month and 3rd months after laser.…”
Section: Discussionsupporting
confidence: 92%
“…As reported in the literature, we report a significant improvement in visual acuity in both groups after YAG-PC. Hossain et al 20 reported an 80% improvement in visual acuity. Likewise, Terry et al 21 and Aron-Rosa et al 22 reported visual improvement in 92%, and 94% of their cohorts, respectively.…”
Section: Discussionmentioning
confidence: 96%
“…Maximum number of patients belonged to the age group of 50-70yrs with the mean age of 59.28 years. Majority of patients had grade I &II PCO and the total amount of energy required to disrupt the posterior capsular opacification (PCO) by YAG laser was found to be directly proportional to grade of posterior capsular opacification (PCO) similar to that reported by Hossain and Hossain(2009) (16) and Bhargawa et al (15). It was observed that a higher energy was needed for posterior capsular opacification (PCO) removal in younger age group patients (17), who usually have thicker opacified posterior capsule following cataract surgery, which is explained by a more active proliferation of posterior capsular cells.…”
Section: E J M Rsupporting
confidence: 78%
“…In another study by Hossain et al (10) ., visual outcome of 500 patients before and after capsulotomy was compared and 80% individuals showed improved visual acuity of ≥6/12.…”
Section: Discussionmentioning
confidence: 89%